Zwischen Eigensinn und Fremdbild: Regionales Binnenmarketing am Beispiel der metropolitanen Region Brandenburg/Berlin - Mahnken, Gerhard (Raumforschung und Raumordnung | Spatial Research and Planning, 2003)
Although intra-regional images play a key role in competition between locations and in marketing regions as a socio-economic and a cultural asset, little attention has hitherto been paid to intra-regional marketing. Yet ideas for the marketing of regions can only be implemented successfully in the long term if the internal image by groups of people native to a region and the external image of potential costumers correspond. Based on the Brandenburg/Berlin region, this contribution examines the issue of how problems and suggested solutions begin to emerge.